Emotional intelligence and transformational leadership among managers in manufacturing companies - Shiau, Wei Chan; Omar, Siti Sarah; Ramlan, Rohaizan; Ahmad, Md Fauzi; Zaman, Izzuddin; Idrus, Nuratiqah (Science Publishing Corporation Inc., 2018)
Despite the fact that numerous studies have been conducted on Emotional Intelligence (EI) and Transformational Leadership (TL), the relationship between EI and TL is yet to be identified. The purpose of this research is to determine the relationship between EI and TL skills among managers in manufacturing companies in Batu Pahat. In this research, a survey questionnaire was administered to fifty managers. Pearson correlation coefficient analysis was employed to test the correlation among variables, including Perceiving Emotion, Facilitating Thought, Understanding Emotion, and Managing Emotion with TL skills. The outcome was that a positive relationship was found between EI and TL skills. This quantitative research is important in providing management with better information regarding the relationship between EI and TL skills among managers so that managers can learn and improve their functions.